Acute toxicity in cervical cancer HIV-positive vs. HIV-negative patients treated by radical chemo-radiation in Zambia. Issue 2 (30th November 2016) - Mdletshe, Sibusiso; Munkupa, Harry; Lishimpi, Kennedy
Abstract : Background: The current standard of radical treatment for patients with cancer of the cervix is combination therapy in the form of radiotherapy with chemotherapy. Generally the same treatment protocol is applied to HIV-positive and HIV-negative patients. However, HIV-positive patients with invasive cervical cancer have not been evaluated in detail regarding treatment response, its toxicities and compliance. Methods: This prospective, quantitative comparative study was conducted to evaluate acute toxicity in radical combination therapy, in HIV-positive (on HAART) and HIV-negative patients for cervical cancer at the Cancer Diseases Hospital, Lusaka, Zambia. In total, 120 stage IB2 –IIIB cervical cancer patients were serially recruited to have an equal number of participants in each arm. Participants received cisplatin-based radical chemo-radiation for five to six weeks and were assessed for acute reactions in four systems: genitourinary, haematopoietic, skin, and gastrointestinal. Toxicity was scored using the NCI CTC v2.0. Results: The results revealed that there was no significant difference with regard to major acute reactions between the two groups. Radical chemo-radiation is therefore well tolerated by HIV-positive patients. Conclusion: Radical chemo-radiation in conventional doses was safely tolerated by a well-selected cervical cancer HIV-positive group on HAART and could be considered suitable for similar patients.